PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE INKUIRI PADA TEMA TOKOH DAN PENEMUAN - N. Neti Runiati (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2019)
The research is motivated by the low student learning outcomes on the theme of Figure and Discovery. The research aims to improve student learning outcomes by using the inquiry method in class VI MIS Emplak Pangandaran Regency. The research method used was Classroom Action Research. The study was conducted in two cycles. Each cycle includes the stages of planning, implementation of actions, observation and reflection. The research subjects were all students of class VI MIS Empal Pangandaran Regency in the first semester of 2019/2020 Academic Year totaling 19 students. The results showed: (1) There was an increase in students' enthusiasm and attention towards the material delivered by the teacher, namely 37% in the first cycle and 79% in the second cycle. (2) There was an increase in student activity, namely 43.5% in the first cycle and 75% in the second cycle. (3) An increase in student learning outcomes is in the first cycle of 66.4% and the second cycle of 73.35%. The results showed an increase in student learning outcomes through the method of inquiry on the theme of the characters and findings on the 1st learning in class VI students of MIS Emplak Pangandaran Regency in the academic year 2019/2019.